Histological and biochemical traits of chilling-injured pulp tissues as affected by cold storage of mango fruit - Wilawan Kumpoun (2018)
© 2017, American Society for Horticultural Science. All rights reserved. Green mango (Mangifera indica L.) ‘Nam Doc Mai See Thong’ fruit were dipped in 2-chloroethylphosphonic acid solution (50 ppm) for 5 minutes, kept at 25 °C for 3 days, cold stored at 5 °C for 35 days and then transferred to 25 °C for 7 days. The skin color of the cold-stored fruit partly changed to dark-brown with surface depression. In addition, desiccated white-corky pulp tissues developed mainly along to the darkbrownish skin. Histological and biochemical analyses revealed that the formation of white-corky pulp tissues was correlated with starch accumulation in the hypodermal cells. Cell wall polymers of the white-corky pulp tissues were characterized by both a lower amount of solubilized pectins and higher amount of hemicelluloses than those of normally ripened (NR) tissues. The highest fatty acid unsaturation was observed in the NR pulps under chilling conditions followed by the white-corky pulp tissues under chilling conditions and the NR tissues without chilling. These results suggested that the disordered membrane caused by chilling inhibited the subsequent cascade of secondary reactions, such as the cell wall degradation. The skin damage derived from chilling injury (CI) is a direct factor inducing abnormal desiccation in the adjacent pulp, resulting in the formation of whitecorky pulp tissues.